Tingkat Motivasi Petani Dalam Menggunakan Bibit Unggul Kelapa Sawit Di Kecamatan Bajubang Kabupaten Batang Hari - Harimurti, Sri; Rusnani, Rusnani; Dewi, Ratna (JALOW | Journal of Agribusiness and Local Wisdom, 2022)
The purpose of this study (1) to determine the level of motivation of farmers to use superior oil palm seeds in Bajubang District (2) to determine the motivational factors of farmers using superior oil palm seeds in Bajubang District. The selection of the research location was based on the consideration that this area contained the most oil palm farmers and had used superior oil palm seeds. The search, collection and processing of data was carried out on August 7 to October 5, 2021. Sampling was carried out using the Accidental Sampling method. To determine the level of motivation of farmers to use high-yielding oil palm seeds in Bajubang District, scoring intervals of 3, 2, and 1 were used with high criteria if there were intervals from 2.34 to 3.00; moderate criteria if any at intervals of 1.67 – 2.33; the last criterion is low if there is an interval of 1.00 – 1.66. The results obtained that the level of motivation of farmers to use superior oil palm seeds in Bajubang District, Batang Hari Regency is high, this can be seen in the average value interval of 2.61. To find out the motivational factors for using superior oil palm seeds in Bajubang District, the F test was carried out. The calculated F value was 3.376, this indicates that the six significant variables simultaneously affect the dependent variable. The value of the regression coefficient on the income variable is 2.478 which is greater than the significant value of 0.549 at the 95% confidence level, meaning that there is a relationship between the income variable and the level of motivation of farmers in using superior seeds in Bajubang District.